Guide for the use and Reporting of Artificial Intelligence in Scientific-Academic Journals - Penabad-Camacho, Liana (2024)
Introduction. Artificial Intelligence (AI) proposes a restructuring of the traditional way of doing and publishing science, since it provides tools that complement, relearn and simplify complex processes typical of research carried out by human beings. The diversity of mechanisms that AI provides demands transparency when reporting its use, and the guarantee that they are consistent with the rigor of scientific communication and its editorial management ecosystem (in which editors, reviewers and authors participate). Aim. This document aims to provide guiding elements for reporting the use of AI in the activities that make up the scientific publication process. Concepts, principles, and recommendations are provided for the three aforementioned roles. They provide literacy and propose learning mechanisms for people who are involved in knowledge communication activities. Guide. Four parts are proposed in the guide. The first one considers a group of concepts necessary to understand the dynamics proposed in the principles and recommendations provided. In particular, the definition of prompts (primary, secondary, and complementary); of the prompt network (or prompt net), and the diagrams that conceptualize its use are proposed. The second part covers editors and editorial teams and offers recommendations for implementing AI-related policies in their journals. The third part gives reviewers good practices for the use of AI to support the process of evaluating a scientific communication unit. The fourth presents an ethical framework and concrete tools, to authors, to use AI in their work and report it in their manuscripts. Final reflection. The goal of using AI must be the common good and improving people’s quality of life. An ethical exercise, which mitigates the introduction of bias or misinformation, must be a core axis for the use of this tool. Keeping in mind that this is an evolving phenomenon is relevant for future updates of the guide and its concepts.